Sustainability reporting in Finnish listed industrial companies : Current state analysis of large-scale companies in Basic Materials and Industrials sectors - Heino, Alisa (My University, 2024)
Sustainability and sustainability reporting have been on growth over the last decade. Sustainability reporting is relevant for today's business, as stakeholders demand consistent and comparable information from companies on their sustainability performance. Reporting has long been voluntary, but regulation and directives have made it mandatory for several companies and this obligation is becoming more and more extensive with the CSRD Directive. This study examines sustainability reporting in Finnish-listed industrial companies, the reporting frameworks they integrate, and the current state of reporting through seven topics of analysis. The study focuses on fourteen case companies, which are large, Finnish public limited companies and operate in the Basic Materials or Industrials sector according to Nasdaq classification. The data consists of sustainability reports published by the case companies either as a stand-alone report or as part of their annual report. The analysis of the study also aims to identify similarities and differences between companies' sustainability reporting and whether the reports are comparable. The results of the research show that companies have published their sustainability information and that it is more common to publish the information as part of an annual report. All case companies have published their sustainability information by implementing GRI standards. Other more common frameworks have also been implemented by the case companies in their reporting or they mention publishing their information elsewhere. Among the seven topics under analysis of the current state, companies exhibit more differences. For some of the aspects analyzed, not every company provides information on their sustainability data, but in general, sustainability reporting by case companies is comprehensive. The results of the research also show that there are differences in the presentation of information, both in terms of presentation and content. The results show that the reports are not comparable as the case companies have published their data in different ways, including the use of various calculation methods. However, in general, compared to previous research, case companies have reported their sustainability performance better than the international average of N100 companies. In the future, the quality and comparability of sustainability reporting can be expected to improve as a result of regulations, directives, and standards.

Kestävä kehitys ja kestävyystietojen raportointi ovat olleet kasvussa viimeisen vuosikymmenen aikana. Kestävyysraportointi on nykypäivän liiketoiminnan kannalta olennaista, sillä sidosryhmät vaativat yrityksiltä johdonmukaisia ja vertailukelpoisia tietoja kestävän kehityksen suorituskyvystä. Raportointi on pitkään perustunut vapaaehtoisuuteen, mutta sääntely ja direktiivit ovat tehneet siitä velvoittavia useille yrityksille ja velvoite laajenee yhä lisää CSRD didektiivin myötä. Tässä tutkimuksessa tutkitaan suomalaisten teollisuuden pörssiyritysten kestävyysraportointia, heidän integroimia raportoinnin viitekehyksiä ja raportoinnin nykytilaa seitsemän analysoitavan kohdan avulla. Tutkimuksessa keskitytään neljääntoista case yritykseen, jotka ovat kooltaan suuria, suomalaisia julkisia osakeyhtiöitä ja toimivat Basic Materials tai Industrials sektorilla Nasdaqin luokituksen mukaan. Tutkimuksen aineisto koostuu case yritysten julkaisemista kestävyysraporteista joko erillisenä raporttina tai osana vuosikertomusta. Tutkimuksen analyysin tarkoituksena on myös selvittää yritysten kestävyysraportoinnin välisiä samankaltaisuuksia, eroavaisuuksia ja ovatko raportit vertailukelpoisi keskenään. Tutkimuksen tulosten mukaan yritykset ovat julkaisseet kestävyystietonsa ja yleisempää on julkaista tiedot osana vuosikertomusta. Kaikki case yritykset ovat julkaiseet kestävyystietonsa implementoiden GRI standardeja. Myös muita yleisimpiä viitekehyksiä ovat case yritykset implementoineet raportointiinsa tai mainitsevat julkaisevansa niiden tiedot muualla. Nykytilan seitsemän analysoitavan kohdan välillä yrityksillä on enemmän eroavaisuuksia. Osaan analysoitavista kohdista ei löydy tietoja jokaiselta yritykseltä heidän kestävyystiedoistaan, mutta pääsääntöisesti case yritysten kestävyysraportointi on kattavaa. Tutkimuksen tulokset osoittavat lisäksi, että raportoinnista löytyy eroavaisuuksia tietojen esittämisessä niin esitystavan kuin myös sisällön osalta. Tulosten mukaan raportit eivät ole keskenään vertailukelpoisia sillä case yritykset ovat julkaiseet tietojaan eri tavalla käyttäen muun muassa erilaisia laskennallisia menetelmiä. Kuitenkin yleisesti case yritykset ovat aiempaa tutkimusta nähden raportoineet kestävyydestään kansainvälisesti N100 yritysten keskiarvoa paremmin. Tulevaisuudessa voidaan odottaa kestävyysraportoinnin laadun ja vertailukelposuuden parantuvan sääntelyn, direktiivien ja standardien myötä.
Keywords: sustainability reporting; sustainable development; Sustainable Development Goals; Global Reporting Initiative; Paris agreement on climate change; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management